High-intensity Interval Training in Different Exercise Modes: Lessons from Time to Exhaustion - Sousa, Ana Catarina; Fernandes, Ricardo J.; Boas, Joao Paulo Vilas; Figueiredo, Pedro (International Journal of Sports Medicine, 2018)
To provide information for high-intensity interval training (HIIT) load, we compared the temporal variables of VO2 response at, and after, a time sustained at the exercise intensity corresponding to VO2max (Tlim) in different exercise modes. Forty-five trained male swimmers (11), rowers (13), runners (10) and cyclists (11) completed an incremental protocol to determine the velocity (vVO2max) or power (wVO2max) at VO2max and a square wave exercise from rest to 100% of vVO2max/wVO2max. The temporal variables of VO2 response were examined using a breath-by-breath gas analyzer. VO2 responses were not different between exercise modes, except for the percentage of VO2max at 50% of Tlim, which was ~6% higher in rowing compared to cycling (97.70±2.90 vs 92.40±5.69%, p=0.013). During the recovery period, both swimmers and rowers evidenced higher percentages of VO2max compared to cyclists at 30 s (65.1±10.4 and 65.7±5.6 vs 52.7±5.6%) and 60 s (41.7±10.8 and 38.4±5.4 vs 30.4±1.8%) time periods, all for p<0.01. Furthermore, swimmers presented higher time values to reach 50% VO2max compared to runners and cyclists (51.1±15.6 vs 38.1±6.7 and 33.8±4.7%; p<0.001). When training at 100% of VO2max intensity, fixed intervals for HIIT could be set freely. However, recovery periods based on time or intensity are exercise-mode dependent.
Keywords: HIIT; VO2max; exercise; recovery